Setting-up a training programme for intraoperative molecular imaging and sentinel node mapping: how to teach? How to learn? - Valdés Olmos, Renato A.; Collarino, Angela; Rietbergen, Daphne D. D.; Pereira Arias-Bouda, Lenka; Giammarile, Francesco; Vidal-Sicart, Sergi (European journal of nuclear medicine and molecular imaging, 2024)
Background The current expansion of image-guided surgery is closely related to the role played by radio-guided surgery in supporting the sentinel node (SN) procedure during more than three decades. The so-called triple approach (lymphoscintigraphy, gamma probe detection and blue dye) was not only essential in the seminal validation of the SN procedure but also a first collective learning effort based on skill transfer and outcome-related evaluation which laid the fundaments to delineate the field of intraoperative molecular imaging (IMI) based on a similar multimodality approach and multidisciplinary practice. Methods These elements are also becoming valid in the current incorporation of SPECT/CT and PET/CT to existing and new protocols of IMI procedures and SN mapping concerning other clinical applications. On the other hand, there is a growing tendency to combine novel modern technologies in an allied role with gamma guidance in the operating room following the development of hybrid tracers and multimodal detection approaches. Against this background, learning initiatives are required for professionals working in this area. Results This objective has led to a group of European practitioners with large experience in SN mapping and IMI applications to give shape to a programme made up out of specific learning modules aimed to be used as a conductive thread in peripherical or centralised training instances concerning the topic. Conclusion The presented work, written as a tutorial review, is placed in an available prior-art context and is primarily aimed at medical and paramedical practitioners as well as at hardware and software developers.